Evaluasi Kinerja Saham Tercatat di Bursa Efek Indonesia Menggunakan Model Sharpe dan Model M² dalam Periode 2003–2007 - Mohamad Samsul (Jurnal Aplikasi Manajemen, 2012)
The research is intended to find out the performance of stock listed in Indonesia Stock Exchange during period of 2003 to 2007 by using M²’s model and Sharpe’s model. The other objective of this research is to find empirical evidence for the different performance of stock between M²’s model and Sharpe’s model.. This research used a number sample of 301 kind of stocks which already listed since before end of the year of 2002 up to end of 2007. This research used monthly data of : stock index prices, market index LQ45, and risk free rate of Indonesia Bank Certificate. Four hypothesis are in this research: (1) the monthly excess return of stock due to M²’s model and Sharpe’s model is different; (2) the risk of stock due to M²’s model and Sharpe’s model is different; (3) the reward to variability ratio due to M²’s model and Sharpe’s model is different; (4) the M² value due to M²’s model and Sharpe’s model is different. The finding of this research show that the number of undervalued stock is 5 stocks and 252 stock according to rank of M²’s model and Sharpe’s model respectively.which the details result as below: The monthly excess return of stock is 0,074 and 0,038 due to M²’s model and Sharpe’s model respectively. The difference is statistically not significant. The risk of stock of 0,155 and 0,237 due to M²’s model and Sharpe’s model respectively. The difference is statistically significant. The reward to variability ratio is 0,478 and 0,166 due to M²’s model and Sharpe’s model respectively. The difference is statistically significant. The M² value is 0,0036 and (0,0157) due to M²’s model and Sharpe’s model respectively. The difference is statistically significant.Keywords: Sharpe’s model, M²’s model, reward to variability ratio, M² value.